The language policy of the language teacher - Risager, Karen (Language at Work - Bridging Theory and Practice, 2010)
Language policy has to do with how far and how one is to act in relation to this complexity. Language policy does not only take place at the macro-level: in international organisations, transnational companies, states, etc., but also at the micro-level; in the interaction between people.